Regularidades empíricas de la inflación en Latinoamérica - Javier Garcia-Cicco; Lorena Garegnani; Maximiliano Gómez-Aguirre; Ariel Krysa; Luis Libonatti (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2022)
– This paper makes a comparative study of the inflation dynamics of Argentina, Brazil, Chile, Colombia, Mexico and Uruguay during the 2004-2019 period. The goal is to document a number of empirical regularities that are useful for some discussions about the determinants and mechanisms of the inflationary processes of those countries. Firstly, we apply a cointegration analysis, and two long-run relationships are found in all the analyzed countries. One relationship is related to the influence of different costs on domestic prices. The other relationship is associated with the money demand. Then, we propose a methodology for decomposing the short-run evolution of the year-on-year inflation between the effects of lagged variables and the contemporary effects of the determinants. As a result, we show that the influence of the inflation persistence explains a big part of the inflation dynamics in Argentina, Uruguay and, to a lesser extent, in Brazil. In Colombia and Mexico, the relative contribution of the autonomous persistence and the lags of the other determinants is more balanced. Finally, in Chile the autonomous persistence has a marginal influence. When focusing on the dynamics influenced by the lagged values of the other determinants, we found heterogeneous explanations in the countries of the sample.
Keywords: C32; E31; 330; Inflation; Latin America; Econometric Models